Placing the Strutt family of Belper, Derbyshire: an historical geography of a late-nineteenth century industrial family - Williamson, Bethany (2022)
The Strutts of Belper have been an important industrial family for understanding how industrial pioneers and paternalists influenced the space they inhabited and manoeuvred through the creation of factory settlements. The earlier generations of the Strutts are notable for their contribution to Derby through ideas of improvement and Enlightenment progressivism demonstrated by William Strutt’s design of the Derbyshire General Infirmary and Joseph Strutt’s funding of the Derby Arboretum. Drawing on ideas of industrial paternalism (Nielson, 2000) and improvement (Billinge, 1996; Conway, 1991; Elliott, 2009), this thesis examines the public lives and civic presence of the later generations of the family which have been somewhat overlooked in comparison to the earlier members. It also investigates the public presence of the female members of the family by drawing on ideas of separate spheres ideology (Davidoff and Hall, 2002; Moore, 2016) and gendered notions of space (Price, 2009). Finally, it contributes to the body of literature that addresses the challenges geographers face when working in archives (Bressey, 2020; Hodder, 2017; McDonagh; 2017).